Reconciliation as Public Theology: Christian Thought in Comparative Indigenous Politics - O’Sullivan, Dominic (International Journal of Public Theology, 2014)
Abstract Christian public theology extends reconciliation beyond its principal sacramental concern for relationships between God and penitent to the construction of ‘socially just’ public relationships for the settlement of intra-national conflict. In theological terms, reconciliation brings public relationships into what Hally calls ‘the Christ narrative of passion, death and resurrection’ in which the perpetrators of injustice repent and seek forgiveness. This article introduces the conflicts that these discourses aim to resolve in Australia, Fiji and New Zealand and explains and contrasts reconciliation’s relative importance in each of these jurisdictions. Moreover, the article’s cross-jurisdictional comparison shows reconciliation’s limits and possibilities as public theology, and argues that in Australia and New Zealand it has helped to create political environments willing to admit indigenous perspectives on a range of policy issues. On the contrary, however, the article also shows that the Fijian churches have distorted the concept of reconciliation to support political imperatives that are difficult to rationalize theologically, even though they are presented by the churches as being concerned with religious goals.
Keywords: christianity; colonisation; kāwanatanga; reconciliation; religion

Globalization and the Politics of Indigeneity - O'Sullivan, Dominic (Globalizations, 2012)
Indigenous peoples inevitably associate globalization with imperial expansion and the colonization of their territories. One associated scholarly view is that globalization's focus on capital accumulation sets aside indigenous cultural priorities to undermine self-determining authority over lands and resources (Fenelon and Hall, 2008; Friedman, 1999; Kelsey, 2005a, 2005b; Stewart-Harawira, 2005). Alternatively, globalization is an ambiguous paradox also providing significant benefits to indigenous peoples. In two very different Pacific countries, Fiji and New Zealand, the globalization of political and jurisprudential thought on the rights of indigeneity provides a significant counter to state assertions of absolute sovereignty. Globalization creates economic opportunities to reduce indigenous dependence on the state and in its contemporary expression is less significant than domestic factors in inhibiting indigenous aspirations. Inevitablemente, la población indígena asocia a la globalización con la expansión imperial y la colonización de sus territorios. Una visión académica asociada es que el enfoque de la globalización en la acumulación de capital, desestima las prioridades culturales indígenas para entorpecer la autoridad autodeterminante sobre la tierra y los recursos. (Fenelon and Hall, 2008; Friedman, 1999; Kelsey, 2005a; 2005b; Stewart-Harawira, 2005). Por otro lado, la globalización es una paradoja ambigua que también provee beneficios a las poblaciones indígenas. En dos países diferentes del Pacífico, Fiyi y Nueva Zelanda, la globalización del pensamiento político o jurisprudencial sobre los derechos del indigenismo, provee una lucha importante contra las afirmaciones estatales de una soberanía absoluta. La globalización crea oportunidades económicas para reducir la dependencia indígena del estado y su expresión contemporánea es menos importante que los factores domésticos que inhiben las aspiraciones indígenas. 伴随着帝国的扩张和其领土的被殖民化，土著居民无可避免地被卷入全球化中。一种相关学术观点认为，全球化对资本积累的关注不顾土著民的文化优先权，损害了土著民对土地和资源的自决权力。（Fenelon 和 Hall, 2008; Friedman, 1999; Kelsey, 2005a; 2005b; Stewart-Harawira, 2005）另一种观点认为，全球化是一种不确定的悖论, 也为土著民带来了巨大利益。在两个截然不同的太平洋国家———斐济和新西兰，关于土著民权利的政治和法律思考的全球化对国家声称的绝对主权提出了挑战。全球化为土著民减少对国家的依赖创造了经济机遇；而且在抑制土著民的权利主张方面，其当今表现作用不及国内因素显著。 원주민들은 불가피하게 세계화를 제국주의적 팽창과 영토의 식민화와 연계시킨다. 관련된 학술적 견해는 자본축적에 초점을 맞춘 세계화가 토지와 자원에 대해서 자결 권위를 약화시키 위하여 원주민들이 문화적으로 우선시 하는 사항을 제켜 놓는다는 것이다 (Fenelon and Hall, 2008; Friedman, 1999; Kelsey, 2005a; 2005b; Stewart-Harawira, 2005). 대안적으로 세계화는 원주민들에게 상당한 이익을 가져다 주는 애모보호한 패러독스이다. 서로 다른 두 태평양 국가인 피지와 뉴질란드에서 원주민의 권리에 대한 정치적, 법률적 사유의 세계화는 절대적 주권을 주장하는 것에 대한 중요한 반론을 제공한다. 세계화는 국가에 의존하는 원주민들의 종속성을 약화시키는 경제적인 기회를 만들고 또한 현대적인 표현으로 내생적인 갈망을 금지시키는데 국내적인 요인들보다 덜 중요하다.
Keywords: globalisation; government; rangatiratanga; sovereignty

Reconciliation: The Political Theological Nexus in Australasian Indigenous Public Policy - O’Sullivan, Dominic (International Journal of Public Theology, 2010)
Reconciliation brings together Christological and anthropological dimensions of human thought to illustrate the nexus between religious principles and political means. For the state reconciliation is concerned with social cohesion and political stability. For the church, it extends the sacramental notion of reconciliation between God and penitent to public relationships. This article examines Roman Catholic contributions to secular reconciliation debates. It shows how religious precepts create moral imperatives to engagement with secular discourses as a necessary element of Christian mission. It also argues that the church’s role in the disruption of indigenous societies creates an additional moral imperative to engage in reconciliation as mission and to articulate a Christian vision of indigenous rights.
Keywords: christianity; kāwanatanga; open access version available; reconciliation; tiriti o waitangi/treaty of waitangi; treaty obligations; treaty settlements

Covenants, Treaties and the Politics of Reconciliation - O'Sullivan, Dominic (Uniting Church Studies, 2010)

Indigeneity, Ethnicity, and the State: Australia, Fiji, and New Zealand - O’Sullivan, Dominic (Nationalism and Ethnic Politics, 2014)
This article draws on the politics of indigeneity to distinguish the claims of first occupancy from simple ethnic identity politics, illustrating that relative political marginalization in Australasia is not so much a function of minority status but of indigeneity itself. The politics of indigeneity's aim is to create political space for self-determination and a particular indigenous share in the sovereign authority of the nation-state itself. The Australasian states are compared with Fiji to demonstrate that the significance of historical constraints on political authority transcend the withdrawal of a colonial power and the restoration of collective indigenous majority population status.

Maori Self-Determination: Towards Differentiated Liberal Citizenship - O'Sullivan, Dominic (Australian Journal of Politics & History, 2019)
During the 1980s and 1990s biculturalism was the ascendant political philosophy for managing the relationship between the New Zealand Crown and the indigenous Maori population. Biculturalism understood Maori politics as a partnership between Maori and the state, grounded in the Treaty of Waitangi, the agreement signed in 1840 from which British government was established. Biculturalism was presented as morally superior to multiculturalism which was understood as setting aside Maori Treaty rights and rights of prior occupancy in favour of less substantive rights available to Maori as one of many ethnic minorities. However, a deeper reading of multicultural political theory provides an instructive critique of biculturalism's inherent limits from the perspective of the Maori right to self-determination. It shows why biculturalism's influence waned. It also shows why Matike Mai o Aotearoa, a blueprint for constitutional transformation commissioned by tribal leaders is unlikely to succeed as a contemporary attempt to reassert biculturalism's influence. Multicultural theory is not a panacea for the right to self-determination, but it does not restrict the development of a broader Maori-centred differentiated liberal citizenship in the ways that biculturalism precludes.
Keywords: Biculturalism; Multicultural; Politics; Self-Determination

Indigeneity: a politics of potential: Australia, Fiji and New Zealand - O'Sullivan, Dominic (Policy Press, 2017)
Keywords: australia; citizenship; government; kāwanatanga; rangatiratanga

Maori self-determination and a liberal theory of indigeneity - O'Sullivan, Dominic (Restoring Indigenous Self-Determination: Theoretical and Practical Approaches, 2014)
Indigenous peoples find themselves locked in power struggles with states and transnational actors who resist their claims, raising important questions in theory and practice. Edited by Marc Woons.
Keywords: rangatiratanga; self-determination; sovereignty

Post Colonialism - O'Sullivan, Dominic (New Zealand Government and Politics, 2015)
Keywords: New Zealand-Politics and government-1972-

Scaling up education reform: addressing the politics of disparity - Bishop, Russell (NZCER Press, 2010)
Keywords: education; educational change; mātauranga māori

The politics of reconciliation in Australia and New Zealand - O’Sullivan, Dominic (Injustice, Memory and Faith in Human Rights, 2017)
This chapter draws on New Zealand examples to contextualize its assessment of reconciliation as public memory in Australian policy discourse. The Treaty of Waitangi has provided the rationale and framework for successive New Zealand governments to say sorry for acts of aggression against Maori tribes. In New Zealand, sorrow is expressed through Acts of Parliament that serve not only as instruments of restitution but as symbols of public memory. Faith and memory are similarly important to wider Christian treaty discourses, as it was Anglican missionaries who drafted the agreement and translated it from English to Maori. The Pastoral letter is drawn into Catholic public memory to justify the development of a public theology of reconciliation. Self-determination belongs first and foremost to individuals, but in Catholic teaching the human person is fundamentally social and exercises the rights and responsibilities of their human being in association with others.
Keywords: reconciliation; religion